Risks of less common cancers in proven mutation carriers with lynch syndrome - Engel, Christoph; Knebel Doeberitz, Magnus von (Journal of clinical oncology, 2012)
Purpose Patients with Lynch syndrome are at high risk for colon and endometrial cancer, but also at an elevated risk for other less common cancers. The purpose of this retrospective cohort study was to provide risk estimates for these less common cancers in proven carriers of pathogenic mutations in the mismatch repair (MMR) genes MLH1, MSH2, and MSH6. Patients and Methods Data were pooled from the German and Dutch national Lynch syndrome registries. Seven different cancer types were analyzed: stomach, small bowel, urinary bladder, other urothelial, breast, ovarian, and prostate cancer. Age-, sex- and MMR gene-specific cumulative risks (CRs) were calculated using the Kaplan-Meier method. Sex-specific incidence rates were compared with general population incidence rates by calculating standardized incidence ratios (SIRs). Multivariate Cox regression analysis was used to estimate the impact of sex and mutated gene on cancer risk. Results The cohort comprised 2,118 MMR gene mutation carriers (MLH1, n = 806; MSH2, n = 1,004; MSH6, n = 308). All cancers were significantly more frequent than in the general population. The highest risks were found for male small bowel cancer (SIR, 251; 95% CI, 177 to 346; CR at 70 years, 12.0; 95% CI, 5.7 to 18.2). Breast cancer showed an SIR of 1.9 (95% CI, 1.4 to 2.4) and a CR of 14.4 (95% CI, 9.5 to 19.3). MSH2 mutation carriers had a considerably higher risk of developing urothelial cancer than MLH1 or MSH6 carriers. Conclusion The sex- and gene-specific differences of less common cancer risks should be taken into account in cancer surveillance and prevention programs for patients with Lynch syndrome.